A NEED ANALYSIS FOR THE TRAINING CURRICULUM MODEL - Nor Hasnida Md Ghazali; Norazilawati Abdullah; Mohd Nazir Md Zabit; Tajul Rosli Shuib; Mahizer Hamzah, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Work-based learning is a learning process carried out in most of a real work environment. It requires students to have the ability to apply those skills in their work environment. Developing a training curriculum model for a course is normally preceded by a need analysis. So, there is a need to do needs analysis. The aim of this study is to determine the generic skills and values required to fulfil the need of the community and the needs for the development of a training curriculum model which is trained based on the work-based learning approach. The study is using a quantitative approach which uses survey method. The samples involved are 43 trainers which are chosen through purposive sampling. Questionnaires are distributed to all the samples. Questionnaires are developed by the researcher. Data is analysed using the Statistical Package for Social Science (SPSS) version 25.0 for frequency, percentage, mean and standard deviation. The overall findings of the study show that there is no educational training either scheduled or application in the course, and there are no direct resources which focuses on generic skills and values elements. They also agree to be trained with all the seven generic skills and five values skills before they join the industry. The implication of the study is that all the elements such as the generic skills and values should be included in the training curriculum module. In conclusion, they need few generic skills and values which contributes to a training curriculum model that can facilitate a better teaching and learning process. Further researchers proposed are to gain data from various educational sector like community colleges and to go for in-depth research such as qualitative approach.